2019
DOI: 10.5380/avs.v24i2.57734
|View full text |Cite
|
Sign up to set email alerts
|

EFEITOS DA APLICAÇÃO DE TRICHLORFON UTILIZADO NO TRATAMENTO DE PARASITOSES SOBRE MÉTRICAS BIOLÓGICAS DE Ctenopharingodon Idella (Valenciennes, 1844)

Abstract: Efeitos da aplicação de trichlorfon utilizado no tratamento de parasitoses sobre métricas biológicas de Ctenopharingodon idella (Valenciennes, 1844)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
1
1
Order By: Relevance
“…Contrary to what was observed in this study with acanthocephalan, Thing et al (2016) found that trichlorfon killed isopod parasites Caecognathia coralliophila within 24 hours at 0.2 mg/L in farmed tiger grouper Epinephelus fuscoguttatus. Regarding withdrawal period, the analyzes of the muscle of grass carp Ctenopharingodon idella revealed that after ve days of the last administration of 0.25 mg/L of tricloforn, no signs of bioaccumulation of the chemical or of its metabolites were found (Guimarães et al, 2019). However, Guimarães et al ( 2019) observed an effect on the growth parameters of C. idella, which was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…Contrary to what was observed in this study with acanthocephalan, Thing et al (2016) found that trichlorfon killed isopod parasites Caecognathia coralliophila within 24 hours at 0.2 mg/L in farmed tiger grouper Epinephelus fuscoguttatus. Regarding withdrawal period, the analyzes of the muscle of grass carp Ctenopharingodon idella revealed that after ve days of the last administration of 0.25 mg/L of tricloforn, no signs of bioaccumulation of the chemical or of its metabolites were found (Guimarães et al, 2019). However, Guimarães et al ( 2019) observed an effect on the growth parameters of C. idella, which was not observed in the present study.…”
Section: Discussioncontrasting
confidence: 73%
“…Trichlorofon, an organophosphate pesticide also used an antiparasitic treatment in aquaculture, can also affect grass carp. One effect of trichlorofon is reduced weight gain; in an experiment that added 0.25 mg/L tricholofon to an aquaculture tank once per week for five consecutive weeks, grass carp exposed to tricholofon had an average weight increase of 17.18%; control group fish had an average weight gain of 53.26% [759]. Exposure to trichlorofon pesticide spraying of the concrete ponds in which they were being held resulted in decreased egg production and egg weight index percentage during spawning in artificially induced female grass carp, with no spawning if water levels were dropped to 50 cm from 1 m [512].…”
Section: Other Toxicants Biotoxinsmentioning
confidence: 99%